Medieval Women, Material Culture, and Power : Matilda Plantagenet and Her Sisters. - Jasperse, Jitske (Leeds : Arc Humanities Press, 2020)
This book argues that the impressive range of belongings that can be connected to Duchess Matilda Plantagenet allows us to perceive elite women's performance of power, even when they are largely absent from the official documentary record.
Intro -- CONTENTS -- LIST OF ILLUSTRATIONS -- USAGE AND CONVENTIONS -- PREFACE -- INTRODUCTION: MATERIAL CULTURE AND PERFORMANCE OF POWER -- Chapter 1. Staging the Bride and her Treasure -- Chapter 2. Small Items Making Big Impressions: Coins and Seals -- Chapter 3. Devotion and Dynasty on Parchment -- Chapter 4. Trappings Vested with Power -- Epilogue: Materializing Power and Its Afterlife -- Select Bibliography -- Index.
Description based on publisher supplied metadata and other sources.
Electronic reproduction. Ann Arbor, Michigan : ProQuest Ebook Central, 2023. Available via World Wide Web. Access may be limited to ProQuest Ebook Central affiliated libraries.
Keywords: Electronic books